ANALISIS ZACHMAN FRAMEWORK DALAM SYSTEM INFORMASI MANAJEMEN KEUANGAN TERPADU SEKOLAH MUHAMMADIYAH - Ahmad Dahlan (UI Cirebon (Universitas Islam Cirebon), 2024)
The era of digital disruption has made all sectors not to be left behind the education sector to make adjustments to the work system from a conventional system to a futuristic system. Especially regarding finance which is an important point for the smooth running of all work programs. Therefore, in school financial management, software is needed that is able to collect financial data under one roof so that it makes it easier for institutions to report financially. The purpose of this study is to analyze the usefulness of Simkatmuh software using Zachman Framework analysis. The research method uses qualitative. The research sample was 6 TU staff of Muhammadiyah schools. Sampling by purposive sampling technique. Data collection techniques use interviews, observations, literature studies, and documentation. The data analysis technique uses descriptive qualitative analysis. The results of the study show that the simkatmuh software is very suitable for use by schools and its benefits are very great for users